USP8‐mediated PTK7 promotes PIK3CB‐related pathway to accelerate the malignant progression of non‐small cell lung cancer - Wencui Kong; Xuegang Feng; Zongyang Yu; Xingfeng Qi; Zhongquan Zhao (Thoracic Cancer)
Abstract Background Protein tyrosine kinase 7 (PTK7) has been found to be highly expressed in non‐small cell lung cancer (NSCLC), but its specific molecular mechanism needs to be further explored. Methods PTK7 mRNA expression in NSCLC tumor tissues was examined by quantitative real‐time PCR. The protein levels of PTK7, ubiquitin‐specific peptidase 8 (USP8), PIK3CB, and PI3K/AKT were determined by western blot. Human monocytes (THP‐1) were induced into macrophages and then co‐cultured with the conditioned medium of NSCLC cells. Macrophage M2 polarization was assessed by detecting CD206+ cells using flow cytometry. The interaction between PTK7 and USP8 or PIK3CB was assessed by Co‐IP assay. Animal study was performed to evaluate the effects of PTK7 knockdown and PIK3CB on NSCLC tumorigenesis in vivo. Results PTK7 expression was higher in NSCLC tumor tissues and cells. After silencing of PTK7, NSCLC cell proliferation, invasion, and macrophage M2 polarization were inhibited, while cell apoptosis was promoted. USP8 enhanced PTK7 protein expression by deubiquitination, and the repressing effects of USP8 knockdown on NSCLC cell growth, invasion, and macrophage M2 polarization were reversed by PTK7 overexpression. PTK7 interacted with PIK3CB, and PIK3CB overexpression could abolish the regulation of PTK7 silencing on NSCLC cell progression. USP8 positively regulated PIK3CB expression by PTK7, thus activating PI3K/AKT pathway. Downregulation of PTK7 reduced NSCLC tumorigenesis by decreasing PIK3CB expression. Conclusion USP8‐deubiquitinated PTK7 facilitated NSCLC malignant behavior via activating the PIK3CB/PI3K/AKT pathway, providing new idea for NSCLC treatment.